Portfolio Analysis Using Malaysia Stock Market Data: Before and During COVID-19 Pandemic - Khah May, She; Wei Yeing, Pan (Enthusiastic : International Journal of Applied Statistics and Data Science, 2022)
This study attempts to evaluate Malaysia’s stock performance before and during COVID-19 across all sectors by using the Sharpe ratio and Sortino ratio with risk measured by standard deviation. We develop an algorithm for stock selection to construct the portfolio investment. In our study, we apply the Sharpe ratio, Treynor ratio and Jensen’s alpha to identify the optimal portfolio. The result shows that the portfolio with stock selection based on the Top 20 Sortino ratio from all stocks is superior to stock selection based on the Top 3 Sortino ratio for each sector. The daily adjusted closing stock prices are collected from March 1, 2019 to December 31, 2021. The result of this study indicates that several sectors are not affected during the COVID-19 pandemic, which are Technology, Industrial, Consumer Products and Services and Property. Hence, investors are suggested to form an optimal portfolio investment based on these sectors. Stock analysts are recommended to imply various risk-adjusted measures to evaluate the portfolio performance with a comprehensive perspective to support the outcome analysis.